Unilateral Vocal Cord Paralysis following Insertion of a Supreme Laryngeal Mask in a Patient with Sjögren’s Syndrome - T. O. J. Masarwa; I. H. F. Herold; M. Tabor; R. A. Bouwman (Case Reports in Anesthesiology)
Since its introduction in 1988 by Dr. Archie Brain, the laryngeal mask airway (LMA) is being used with increasing frequency. Its ease of use has made it a very popular device in airway management and compared to endotracheal intubation it is less invasive. The use of LMA was on the rise, so has been the incidence of its related complications. We report severe unilateral vocal cord paralysis following the use of the supreme laryngeal mask (sLMA) in a patient with Sjögren’s syndrome. In addition, we propose possible mechanisms of injury, review the existing case reports, and discuss our findings.